Study on impact fatigue test and life prediction method of TC18 titanium alloy. (March 2023) - Binwen, Wang; Chengcheng, Qian; Chunyu, Bai; Weiping, Hu; Zhixin, Zhan; Qiang, Yang; Yupei, Guo; Biao, Wang
Highlights: A new CDM based impact fatigue damage model is proposed with considering the effect of strain rate. The conventional low-cycle fatigue test data combined with a few impact fatigue test data are used to calibrate the parameters of the damage model. The numerical method for the impact fatigue damage calculation is proposed and implemented. The impact fatigue life prediction results agree well with the experimental data. Abstract: To study the impact fatigue properties of TC18 titanium alloy and propose a new damage model for the impact fatigue life prediction of material, the impact fatigue test method and the impact response measurement scheme are designed. The impact fatigue tests are then implemented on a drop hammer impact test machine to obtain the fatigue lives and impact responses of the tested specimens under different impact conditions. A new impact damage model is proposed based on the theory of continuum damage mechanics considering the effect of strain rate. The calibration method of material parameters is presented, and the parameters of the impact damage model are obtained according to the test data of TC18. Afterward, the numerical implementation of impact damage calculation is established, and an ABAQUS user-defined subroutine is used to realize the finite element numerical simulation of impact fatigue damage accumulation. Finally, the damage evolution of TC18 under tensile impact fatigue loading is simulated and the corresponding fatigue life is predicted. The errors between the calculated impact fatigue lives and the experimental lives are less than 25%, which demonstrates the good validity and applicability of the proposed damage model and the numerical method.